Reduced BCL2 and CCND1 mRNA expression in human cervical cancer HeLa cells treated with a combination of everolimus and paclitaxel - Yilmaz, Akin; Alp, Ebru; Onen, H. Ilke; Menevse, Sevda (Contemporary Oncology/Współczesna Onkologia, 2016)
Aim of the study : Cervical cancer is the second most common malignancy in women worldwide. Everolimus displays direct effects on growth and proliferation of cancer cells via inhibition of mammalian target of rapamycin (mTOR) protein, which is known to be associated with drug resistance. In this study, we aimed to investigate the effects of everolimus, gemcitabine, and paclitaxel in terms of cell viability and mRNA expression levels of GRP78, CCND1, CASP2, and BCL2 genes. Material and methods : HeLa cells were treated with different doses of everolimus, gemcitabine, and paclitaxel. Cell viability was assessed using MTT assay, and obtained dose response curves were used for the calculations of inhibitory concentration (IC) values. At the end of the treatment times with selected doses, RNA isolation and cDNA synthesis were performed. Finally, GRP78, CCND1, CASP2, and BCL2 genes mRNA expression levels were analysed using quantitative PCR. Results : The IC50 value of everolimus was 0.9 µM for 24-hour treatment. Moreover, the IC50 value of gemcitabine and paclitaxel was found to be around 18.1 µM and 7.08 µM, respectively. Everolimus, gemcitabine, and paclitaxel treatments alone did not change the GRP78, CCND1, BCL2 and CASP2 mRNA expression levels significantly. However, combined treatment of everolimus and paclitaxel significantly reduced BCL2 and CCND1 mRNA expression (p 0.05). Conclusions : Down-regulation of CCND1 and BCL2 expression may be an important mechanism by which everolimus increases the therapeutic window of paclitaxel in cervical cancers.